The Role of Forensic Accounting in Mitigating Tax Fraud : An Analysis of its Effectiveness in Nigeria - Paramole, Ibrahim Babatunde (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2025)
Tax evasion, fraud, and money laundering significantly challenge Nigeria’s economic stability and governance. This research investigates the pervasive issues of tax fraud and evasion in Nigeria, significantly undermining government revenue and public trust. The study explores the role of forensic accounting in combating these financial crimes within Nigeria’s legal framework. A case study approach was employed, analysing specific instances of tax fraud and the effectiveness of forensic accounting interventions in addressing these challenges. The data collection technique in this study is through semi-structured interviews. Data collected from analyses using thematic analysis. The findings reveal that, despite existing legislation, enforcement is hindered by corruption, inadequate resources, and a lack of public awareness. The case studies illustrate how forensic accounting is a critical tool for detecting and preventing tax fraud; however, its application is often limited due to insufficient training and poor inter-agency collaboration. The findings reveal a persistent culture of non-compliance fueled by systemic corruption, ineffective enforcement mechanisms, and limited public awareness of tax obligations. Furthermore, the research uncovers a significant gap in the capacity and application of forensic accounting practices, which hampers effective fraud detection and prevention. In conclusion, the research underscores the urgent need for enhanced regulatory frameworks, public awareness initiatives and better integration of forensic accounting practices to address tax-related crimes effectively. This study contributes to the body of knowledge by providing actionable recommendations for policymakers and practitioners and establishing a foundation for future research on financial crimes in Nigeria. The findings of this study have significant implications for Nigeria's tax and financial system. The close links between tax evasion, fraud, and money laundering have created a vicious circle that eats away at national revenues and undermines public trust in government institutions. To address these challenges, comprehensive reforms to the Nigerian tax system are recommended with a focus on simplifying tax regulations, closing legal loopholes, and strengthening enforcement mechanisms.